(3oeYLe GdTjhNs - (3CHh HcQ CMeO Hf EHQGgje Hf ESeGYjd GdESeGYjdj GdLQLGfj, GdESeGYjdj,J (B371 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN GdYGde TgGH GOjf CHhGdaVd eMeO Hf jhSa Hf Ydj GdZRfhj s
(3HChdgG hBNQgG SeGYGJ cKjQI HNWhW HYV GdYdeGAs
(3JHUQI GdYfhGf (B:s
(3QhGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B86s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B147 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1735s
Keywords: (3GdJGQjNs